Challenge of vegetation greening on water resources sustainability: Insights from a modeling‐based analysis in Northwest China. Issue 7 (10th February 2017) - Tian, Fei; Lü, Yi He; Fu, Bo Jie; Zhang, Lu; Zang, Chuan fu; Yang, Yong Hui; Qiu, Guo Yu
Abstract: Forest restoration policies are often implemented without the assessment of their full environmental impact. In this study, we investigated the challenges of vegetation greening resulted from forest restoration on water resource sustainability, using a model‐based simulation in northwestern China. Four different vegetation scenarios and 25 future climate scenarios were employed using the Soil and Water Assessment Tool model. Results suggest that (a) the mean annual evapotranspiration changes from only 7.2% in the barren case to 100% in the forest case; however, it produced a 35.2% reduction in average annual streamflow and a 157% increase in soil water storage. The upstream vegetation greening caused the enhancement of water retention, while also creating great challenges for future downstream water resource sustainability; (b) seasonal effect was significant in that 100% forest case increased evapotranspiration (+40%) but it also reduced the streamflow (−73%) compared to the barren case in growing season, which may exacerbate spring and summer drought; (c) changes of evapotranspiration and streamflow were only 0.3% and −0.9% at T + 3.9 °C when compared to the historic scenario in barren cases, while for all forest cases, variations were 3% and −21.8%, respectively; (d) vegetation greening induced more remarkable changes in hydrological components than those resulting from climate change. Our "what if" research provides new insights for promoting sustainable management of water resources and ecosystems in mountainous water source areas.